2008
DOI: 10.1097/jom.0b013e318165c7ec
|View full text |Cite
|
Sign up to set email alerts
|

Val/Met Polymorphism of the COMT Gene Moderates the Association Between Job Strain and Early Atherosclerosis in Young Men

Abstract: Our findings support a general model in which the interaction between genotype and job strain is assumed to predispose to increased atherosclerotic processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 52 publications
0
14
0
2
Order By: Relevance
“…Two studies reported an association in males and not females. 29,30 Two other studies found the opposite to be true. 31,32 Differences in the WRS-CIMT association in males were found to be modified by a genetic factor.…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…Two studies reported an association in males and not females. 29,30 Two other studies found the opposite to be true. 31,32 Differences in the WRS-CIMT association in males were found to be modified by a genetic factor.…”
mentioning
confidence: 84%
“…Hintsanen et al and Nordstrom et al found a relationship between work related stress and increased CIMT in males, but observed no association among females. 29,30 Conversely, two studies found a relationship between WRS and CIMT in females, but not males. 31,32 Differences in smoking, BMI, and hypertension across studies may explain these conflicting results.…”
Section: Summary Of Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…the mean age of the women was 52.8 yr, but the job demand was assessed by only 3 items which may not have reflected the job stress adequately leading to null findings. Recently, some studies reported that certain genotypes moderate the association between job stress and the risk of CHD 34,35) . It may be important to explore whether different races have genotypic variation that may moderate this association.…”
Section: Discussionmentioning
confidence: 99%